Oxidative Fluorination of Cu/ZnO Methanol Catalysts. (3rd July 2019) - Dybbert, Valentin; Fehr, Samuel Matthias; Klein, Florian; Schaadt, Achim; Hoffmann, Anke; Frei, Elias; Erdem, Emre; Ludwig, Thilo; Hillebrecht, Harald; Krossing, Ingo
Abstract: The influence of a mild difluorine treatment on Cu/ZnO precatalysts for methanol synthesis was investigated. It led to the incorporation of 1.2…1.3±0.1 wt % fluoride into the material. Fluorination considerably increased the amount of ZnOx related defect sites on the catalysts and significantly increased the space‐time yields. Although the apparent activation energy E A, app for methanol formation from CO2 and H2 was almost unchanged, the E A, app for the reverse water‐gas shift (rWGS) reaction increased considerably. Overall, fluorination led to a significant gain in methanol selectivity and productivity. Apparently, also the quantity of active sites increased. Abstract : Fluorierte Katalysatoren…? Durch die Exposition von Cu/ZnO‐Präkatalysatoren gegenüber gasförmigem F2 wurde Fluorid in das Material eingebracht. Nach der Aktivierung änderten sich die katalytischen Eigenschaften der F‐Cat‐Systeme signifikant, wodurch die Leistung für die Methanolsynthese erhöht und diejenige für die reverse Wasser‐Gas‐Shift‐Reaktion ausgehend von CO2 und H2 verringert wurde.